Literasi Numerasi pada Pembelajaran Tematik Terpadu di Kelas Rendah Sekolah Dasar - Dewi Nadhila Ashri; Heni Pujiastuti (Jurnal Karya Pendidikan Matematika, 2021)
This study aims to describe numeracy literacy in integrated thematic learning in the lower grades of elementary school. The participants in this study were low grade students, that is grades 1,2 and 3 of Elementary School. This study uses a descriptive type of qualitative method. The type of data collected is the result of problem solving done by the participants. Data collection techniques in this study using tests. The test instrument consists of several literacy questions and numeracy questions. Based on the results of the research, students can work on literacy questions well even though the accuracy in working on the questions is still lacking, while in the matter of numeracy which is numeracy literacy errors are still found so that students' numeracy literacy skills still need to be improved.